A integração de dados físico-naturais e antrópicos para a análise de risco à inundação na cidade de Limeira SP - Santos, Luís Fernando Riquetti dos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In the last decades, the process of urbanization has been intensifying, however, without adequate planning, subjecting the population to situations of risk, due to the frequent disasters that occur in the cities. In this context, floods, flooding is an example of these often occurring disasters reaching many municipalities of the country, as well as most of the cities that have settled in the vicinity of rivers and streams, resulting in socioeconomic and environmental impacts. Thus, this study aimed to identify areas susceptible to flooding, through the integration of physical-natural and anthropic aspects of the urban area of Limeira SP, with support in geotechnologies. For this purpose, thematic maps (Hypsometric, Declivity, Land Use and Permanent Preservation Areas) were integrated through the multi-criteria analysis to elaborate the flood susceptibility map. Rainfall data were also analyzed, considering a period of 9 years (2010 to 2018), as well as the Flood Occurrences identified in news from local newspapers, in order to correlate rainy years with flood events. The results obtained in this research allowed to identify and classify flood risk areas, being compared with flood and flood points published in the newspapers, which allowed to confirm the critical points and indicate areas more susceptible to future events (for example, the marginal Tatu and the banks of the Vista Alegre stream). Also, it was possible to analyze the areas of use conflicts in Areas of Permanent Preservation (APP), being verified degraded sectors, covering constructed areas and grasses. During the course, 12 field studies were carried out to analyze and characterize the risk areas; acquire samples (photos) for the land use map and application of the questionnaires. The results of this research may serve as a subsidy to the municipal public administration, aiming at an adequate planning of the use of urban land

Nas últimas décadas, o processo de urbanização vem se intensificando, contudo, sem um planejamento adequado, submetendo a população a situações de risco, devido aos desastres frequentes que ocorrem nas cidades. Neste contexto, as enchentes, inundação é um exemplo desses desastres que ocorrem frequentemente, atingindo muitos municípios do país, assim como a maioria das cidades que se instalaram nas proximidades de rios e córregos, resultando em impactos socioeconômicos e ambientais. Assim, este estudo teve como objetivo identificar as áreas susceptíveis à inundação, através da integração de aspectos físico-naturais e antrópicos da área urbana de Limeira SP, com apoio nas geotecnologias. Para o propósito, foram integrados mapas temáticos (Hipsométrico, Declividade, Uso da Terra e Áreas de Preservação Permanente) através da análise multicritérios, para elaborar o mapa de Suscetibilidade à Inundação. Os dados pluviométricos também foram analisados, considerando-se um período de 9 anos (2010 a 2018), assim com as Ocorrências de Inundação identificadas em notícias de jornais locais, a fim de correlacionar os anos de chuvas com as ocorrências de inundações. Os resultados obtidos nessa pesquisa permitiram identificar e classificar as áreas de risco de inundação, sendo comparado com os pontos de alagamento e inundação divulgados nos jornais, os quais permitiram confirmar os pontos críticos e indicar áreas mais susceptíveis a ocorrências futuras (por exemplos, a marginal Tatu e as margens do córrego Vista Alegre). Também, foi possível analisar as áreas de conflitos de usos em Áreas de Preservação Permanente (APP), verificando-se setores degradados, abrangendo áreas construídas e gramíneas. No decorrer, foram realizados 12 trabalhos de campo, para análise e caracterização das áreas de risco; adquirir amostras (fotos) para o mapa de uso da Terra e aplicação dos questionário...
Keywords: Inundações; Urbanização; Planejamento urbano; Geotecnologia ambiental; Chuvas - 2010-2018; Área de preservação permanente; Sistemas de informação geográfica; Limeira (SP)